2017
DOI: 10.1177/0954407017728849
|View full text |Cite
|
Sign up to set email alerts
|

Exergo-technological explicit methodology for gas-turbine system optimization of series hybrid electric vehicles

Abstract: Significant research efforts have been invested in the automotive industry on hybrid electrified powertrains in order to reduce the dependence of passenger cars on oil. Electrification of powertrains resulted in a wide range of hybrid vehicle architectures. The fuel consumption of these powertrains strongly relies on the energy converter performance, as well as on the energy management strategy deployed on board. This paper investigates the potential of fuel consumption savings of a series hybrid electric vehi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 30 publications
1
27
0
Order By: Relevance
“…The identified realistic GT-system options of Bou Nader et al 5 (Figure 3) are assessed here in order to account for their energy efficiency and net specific work. The assessment methodology for each option is illustrated in Figure 2.…”
Section: Energetic Analysis Of the Different Gt-system Optionsmentioning
confidence: 99%
See 2 more Smart Citations
“…The identified realistic GT-system options of Bou Nader et al 5 (Figure 3) are assessed here in order to account for their energy efficiency and net specific work. The assessment methodology for each option is illustrated in Figure 2.…”
Section: Energetic Analysis Of the Different Gt-system Optionsmentioning
confidence: 99%
“…As for the compression work, it was demonstrated that the use of an intercooler to reject heat during the compression phase is technically feasible and induces an increase in the efficiency and net specific work of the system. 5,1618…”
Section: Energetic Analysis Of the Different Gt-system Optionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The powertrain modelling, sizing and equations are presented in [10]. The electric traction motor is sized in order to ensure similar performance to a medium class hybrid vehicle, with maximum speed of 160 km/h and acceleration from 0-100 km/h in 9.6 s. Consequently, an 80kW tractive power electric machine is selected.…”
Section: A Powertrains Setup Components Sizing and Energy Managemenmentioning
confidence: 99%
“…As for the capacity, three different values of 5, 10 and 20 kWh are considered in the analysis in order to assess the impact of the battery size on improving fuel consumption. The additional battery mass is taken into account and values were retrieved from [10].…”
Section: A Powertrains Setup Components Sizing and Energy Managemenmentioning
confidence: 99%